Potential of Secretome Hydrogel for Wound Healing in LPS- and Scratch-Induced BJ Cells as an Inflammation Model - Widowati, Wahyu; Rahmat, Deni; Faried, Ahmad; Nainggolan, Ita Margaretha; Priyandoko, Didik; Wargasetia, Teresa Liliana; Sugiaman, Vinna Kurniawati; Triharsiwi, Dwi Nur; Qlintang, Sandy; Murti, Harry; Azis, Rizal; Jeffrey, Jeffrey (Research Center of Inorganic Materials and Coordination Complexes, FMIPA Universitas Sriwijaya, 2025)
Wound healing often requires specialized interventions to accelerate recovery due to prolonged inflammation and limited regenerative factors. Umbilical Cord Mesenchymal Stem Cells secretome (UCMSCs) comprises various cytokines and growth factors that can promote wound healing. This study aims to analyze the potential of a secretome-based hydrogel as a wound-healing agent using BJ fibroblast cells induced by lipopolysaccharide (LPS) and scratch injury as an inflammation model. The secretome hydrogel was formulated using Carbopol, Hydroxypropyl Methylcellulose (HPMC), Hydroxyethyl Cellulose (HEC), and secretome. Cytotoxicity was conducted using the WST-8 assay, while cell migration was evaluated through a scratch assay. Tumor Necrosis Factor-???? (TNF-????), Nuclear Factor kappa-B (NF-????B), and Interleukin-8 (IL-8) gene expression were analyzed via qRT-PCR. Additionally, malondialdehyde (MDA) levels were measured for oxidative stress assessment, whereas Connective Tissue Growth Factor (CTGF) and Transforming Growth Factor-????1 (TGF-????1) levels were quantified using ELISA and colorimetric assays. The secretome hydrogel exhibited no cytotoxic effects on BJ fibroblast cells and significantly enhanced cell migration. Moreover, it reduced the TNF-????, IL-8, and NF-????B expression, indicating anti-inflammatory activity. The hydrogel also decreased MDA levels while increasing TGF-β1 and CTGF expression, suggesting antioxidant properties and enhanced tissue regeneration in the inflammatory model. The secretome-based hydrogel presents a promising therapeutic approach for promoting chronic wound healing by modulating inflammation, reducing oxidative stress, enhancing tissue regeneration, and stimulating fibroblast migration.